Pengaruh Sustainability Report Disclosure dan Audit Tenure terhadap Nilai Perusahaan pada Sektor Energi Tahun 2020–2024 - Naccir Sidabutar; Valentine Siagian; Judith Tagal Gallena Sinaga (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study was conducted to examine the effect of Sustainability Report and Audit Tenure disclosure on company value in the energy sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The approach used was a quantitative method using secondary data collected through annual reports, selected reports, and company audit reports. A purposive sampling technique was applied with the criteria of energy companies listed on the IDX during the study period. Data analysis included descriptive statistics, normality tests, multiple linear regression tests, multicollinearity tests, partial tests, and simultaneous tests to obtain a comprehensive picture of the relationship between the research variables. The results of the study proved that sustainability report disclosure had a significant and negative effect on company value, while audit tenure had no significant effect on company value. These findings emphasize the importance of transparency in financial reporting and independent audit policies to strengthen investor confidence, as well as the need for companies to balance the costs of implementing a decommissioning program with the economic benefits generated in the long term to support company performance.